Additions and corrections to the Catalogue of the Heteroptera of the Palaearctic Region: Tingidae of the Balkan peninsula - Protić, Ljiljana (Acta entomologica slovenica (Ljubljana), 2004)
The Catalogue of the Palaearctic Heteroptera is supplemented with 32 overlooked records on the distribution of species of the family Tingidae. For 50 Tingid species the changes in political boundaries are considered.
Keywords: Balkanski polotok; Heteroptera; insekti; stenice; zoogeografija